2023
DOI: 10.1007/s00784-023-05219-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of tooth-supported monolithic zirconia vs. porcelain-veneered zirconia fixed dental prosthesis, with an additional focus on the cement type: a systematic review and meta-analysis

Shahed Shihabi,
Bruno Ramos Chrcanovic

Abstract: Purpose To compare the failure rates and the prevalence of technical complications between full-coverage tooth-supported monolithic zirconia (MZ) and porcelain-veneered zirconia (PVZ) fixed dental prosthesis, based on a systematic literature review. Methods An electronic search was performed in three databases, supplemented by hand searching. Several statistical methods were used. Results Seventy-four publications r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Through the use of computer-aided design/computer-aided manufacturing (CAD/CAM), the production of such ceramic crowns is less time-consuming and decreases the presence of internal defects and technical variations when compared to the conventional bilayer systems [ 1 3 ]. Besides, previous studies reported higher mechanical performance and survival rates for monolithic restorations than for veneered zirconia [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of computer-aided design/computer-aided manufacturing (CAD/CAM), the production of such ceramic crowns is less time-consuming and decreases the presence of internal defects and technical variations when compared to the conventional bilayer systems [ 1 3 ]. Besides, previous studies reported higher mechanical performance and survival rates for monolithic restorations than for veneered zirconia [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%